2016
DOI: 10.18410/jebmh/2016/572
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year Histopathological Review of CNS Tumours in a Tertiary Centre With Emphasis on Diagnostic Aspects of Uncommon Tumours

Abstract: BACKGROUND Tumours of central nervous system (CNS) are of varied histogenesis and show divergent lines of differentiation and morphological features. These tumours show specific predilection for age and sex groups, more commonly than of tumours of other systems. Though tumours of glial tissue are more common, other tumours of neural, ependymal and meningeal origin are not uncommon. Metastatic disease is the common encounter in elderly. Tumour diagnosis is not always straight forward as many non-neoplastic lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…The majority of CNS neoplasms are astrocytic tumours similar to other studies conducted by Jalai et al 7 and Javaria et al 8 but different from study conducted by Pidakala et al 9 The most malignant and frequent being glioblastoma multiforme, as also evidenced by our study. 10,11 In previous studies, incidence rates were higher for men.…”
Section: Cns Tumoursupporting
confidence: 83%
“…The majority of CNS neoplasms are astrocytic tumours similar to other studies conducted by Jalai et al 7 and Javaria et al 8 but different from study conducted by Pidakala et al 9 The most malignant and frequent being glioblastoma multiforme, as also evidenced by our study. 10,11 In previous studies, incidence rates were higher for men.…”
Section: Cns Tumoursupporting
confidence: 83%
“…7,14 However, other studies by Mondal, Vimal et al, Hema et al, Kanthikar et al, Khonglah et al, Mehta et al, Pidakala et al showed higher percentage of schwannomas ranging from 6.1 to 18.05%. 5,6,9,11,13,16,23 In our study meningiomas showed slight female preponderance similar to that of studies by Vimal, Jaiswal et al, Khonglah et al, Mohammad et al and Mehta et al while Hamdani et al showed male dominance. 5,7,9,13,14,16 Meningothelial meningioma was the commonest type in this study as previously noted by Vimal et al 13 Glioblastoma were commonest astrocytoma with 57.58% of total astrocytoma.…”
Section: Figure 5: Distribution Of Intracranial Cns Tumours In Adult Population (N=84)supporting
confidence: 90%
“…5,13 Frontal and the fronto-parietal lobe (16 cases each) were the commonest location for the tumours in our study. 5,9,[12][13][14]23 Sumathi et al and Lakshmi et al found parietal lobe being common followed by frontal lobe. 21,8 Out of total cases, supratentorial tumours were common (75.25%).…”
Section: Figure 5: Distribution Of Intracranial Cns Tumours In Adult Population (N=84)mentioning
confidence: 99%
“…Other studies have shown similar data with occasional study showing astrocytomas to be more common. 1,2,8,19 Research has shown multiple genetic and environmental risk factors for meningiomas. Genetically, it is known to be associated with neurofibromatosis type II and multiple endocrine neoplasia type I.…”
Section: Discussionmentioning
confidence: 99%
“…CNS tumors diagnosis is often difficult as general pathologist lack experience and non-neoplastic processes mimic tumors and primary needs to be differentiated from secondaries. [1][2][3][4] The most prevalent primary CNS tumors in adults are astrocytic tumors followed by meningiomas. Numerous classifications have been put forth to classify tumors since 1979, which was based on light microscopy.…”
Section: Introductionmentioning
confidence: 99%